Mapping the Landscape of Customer Trust Research: Trends and Future Opportunities - Raditya, Koen Raffy; Lim, Rita Amelinda (Journal of International Conference Proceedings, 2025)
This study conducts a bibliometric and scientific mapping analysis of Customer Trust research from 1985 to 2024, aiming to explore publication trends, key contributors, influential journals, and thematic developments. Using Scopus data and tools like VOSviewer, the findings reveal a steady growth in publications, with peak citation impact during 2019–2020, followed by a citation lag in later years. Analysis shows that research influence is more closely linked to quality than quantity, with the International Journal of Bank Marketing and Universiti Sains Malaysia emerging as leading contributors. Thematic mapping identifies three primary clusters—Digital Trust, Online Trust, and Perceived Value—all anchored by customer satisfaction as a central theme. These results demonstrate that Customer Trust has evolved into a dynamic construct shaped by technological innovation, online behavior, and perceived corporate value. Future research should integrate interdisciplinary approaches, emphasizing digital ecosystems, ethical practices, and corporate responsibility to deepen the theoretical and practical understanding of Customer Trust in a rapidly transforming digital landscape.